Peran Qana'ah dalam Menurunkan Fear of Missing Out (FOMO) pada Era Media Sosial: Sistematis Literatur Review - Elfira Rosa Karnaini; Raydez Krida Wiratama; Rahamdianti Aulia (CV. ITTC INDONESIA, 2026)
Fear of Missing Out (FOMO) has emerged as a significant psychological phenomenon in the social media era, characterized by anxiety stemming from the perception of being excluded from others' experiences. Although various interventions have been developed to mitigate FOMO, studies integrating Islamic spiritual constructs, particularly qana'ah (contentment), remain scarce. This study aims to identify, evaluate, and synthesize scientific evidence regarding the potential role of qana'ah in reducing FOMO, as well as to construct a conceptual framework applicable to Muslim communities. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines, with article searches performed through Google Scholar using relevant keywords covering publications from 2021 to 2026. Of 150 initially identified articles, 8 met the inclusion criteria and were subjected to in-depth analysis. The synthesis revealed three major themes: (1) qana'ah as a spiritual coping mechanism against FOMO, (2) psychological pathways linking qana'ah to reduced FOMO through diminished social comparison and strengthened internal orientation, and (3) strategies for internalizing qana'ah through education, spiritual development, and Islamic-based digital literacy. The findings indicate that qana'ah holds significant potential as a protective factor against FOMO by enhancing psychological resilience and reducing reliance on digital social validation. Future empirical research employing experimental designs and standardized measurement instruments is warranted.